Microclimate structures communities, predation and herbivory in the High Arctic. Issue 4 (13th January 2021) - Kankaanpää, Tuomas; Abrego, Nerea; Vesterinen, Eero; Roslin, Tomas
Abstract: In a warming world, changes in climate may result in species‐level responses as well as changes in community structure through knock‐on effects on ecological interactions such as predation and herbivory. Yet, the links between these responses at different levels are still inadequately understood. Assessing how microclimatic conditions affect each of them at local scales provides information essential for understanding the consequences of macroclimatic changes projected in the future. Focusing on the rapidly changing High Arctic, we examine how a community based on a common resource species (avens, Dryas spp.), a specialist insect herbivore ( Sympistis zetterstedtii ) and natural enemies of lepidopteran herbivores (parasitoids) varies along a multidimensional microclimatic gradient. We ask (a) how parasitoid community composition varies with local abiotic conditions, (b) how the community‐level response of parasitoids is linked to species‐specific traits (koino‐ or idiobiont life cycle strategy and phenology) and (c) whether the effects of varying abiotic conditions extend to interaction outcomes (parasitism rates on the focal herbivore and realized herbivory rates). We recorded the local communities of parasitoids, herbivory rates on Dryas flowers and parasitism rates in Sympistis larvae at 20 sites along a mountain slope. For linking community‐level responses to microclimatic conditions with parasitoid traits, we used joint species distribution modelling. We then assessed whether the same abiotic variables also affect parasitism and herbivory rates, by applying generalized linear and additive mixed models. We find that parasitism strategy and phenology explain local variation in parasitoid community structure. Parasitoids with a koinobiont strategy preferred high‐elevation sites with higher summer temperatures or sites with earlier snowmelt and lower humidity. Species of earlier phenology occurred with higher incidence at sites with cooler summer temperatures or later snowmelt. Microclimatic effects also extend to parasitism and herbivory, with an increase in the parasitism rates of the main herbivore S. zetterstedtii with higher temperature and lower humidity, and a matching increase in herbivory rates. Our results show that microclimatic variation is a strong driver of local community structure, species interactions and interaction outcomes in Arctic ecosystems. In view of ongoing climate change, these results predict that macroclimatic changes will profoundly affect arctic communities. Abstract : The authors' study shows that parasitoid communities in the Arctic are structured by microclimatic conditions in the landscape. Promisingly, responses of individual species can be, in part, understood by their life‐history traits. This will help when making general predictions on future trajectories of community and ecosystem change.